CXCR4-SDF-1 interaction potentially mediates trafficking of circulating tumor cells in primary breast cancer. Issue 1 (December 2016) - Mego, M.; Cholujova, D.; Minarik, G.; Sedlackova, T.; Gronesova, P.; Karaba, M.; Benca, J.; Cingelova, S.; Cierna, Z.; Manasova, D.; Pindak, D.; Sufliarsky, J.; et al.
Abstract Background Cytokines are involved in cancer invasion and metastasis. Circulating tumor cells (CTCs) play key role in tumor dissemination and are an independent survival predictor in breast cancer patients. The aim of this study was to assess correlation between CTCs and plasma cytokines in primary breast cancer (PBC) patients. Methods This study included 147 chemotherapy naïve PBC patients. Peripheral blood mononuclear cells (PBMC) were depleted of hematopoetic cells using RossetteSep™ negative selection kit. RNA extracted from CD45-depleted PBMC was interrogated for expression of EMT (Twist1, Snail1, Slug, Zeb1) and epithelial (Ck19) gene transcripts by qRT-PCR. The concentrations of 51 plasma cytokines were measured using multiplex bead arrays. Results CTCs were detected in 25.2 % patients. CTCs exhibiting only epithelial markers (CTC_EP) and only EMT markers (CTC_EMT) were present evenly in 11.6 % patients, while CTCs co-expressing both markers were detected in 2.0 % patients. Patients with presence of CTC_EP in peripheral blood had significantly elevated levels of plasma IFN-α2, IL-3, MCP-3, β-NGF, SCF, SCGF-β, TNF-β and SDF-1 compared to patients without CTC_EP. CTC_EP exhibited overexpression of SDF-1 receptor and CXCR4, but not other corresponding cytokine receptor, and in multivariate analysis SDF-1 was independently associated with CTC_EP. There was an inverse correlation between CTC_EMT and plasma cytokines CTACK, β-NGF and TRAIL, while presence of either subtype of CTCs was associated with increased level of TGF-β2. Conclusion Using cytokine profiling, we identified cytokines associated with CTCs subpopulations in peripheral blood of PBC. Our data suggest that CXCR4-SDF-1 axis is involved in mobilization and trafficking of epithelial CTCs.